Integration of International Classification of Diseases Version 11 Application Program Interface (API) in the Rwandan Electronic Medical Records (openMRS): Findings from Two District Hospitals in Rwanda. - MUGISHA, Michael; BYIRINGIRO, Baptiste; UWASE, Melissa; ABIZEYIMANA, Theophile; NDIKUBWIMANA, Berchmas; KAREMA, Nadine; KAYIGANWA, Michele; TRAN NGOC, Candide; KOSTANJSEK, Nenad; CELIK, Can; MARC, Donada; TWIZERE, Celestin; et al. (Studies in Health Technology & Informatics, 2020)
World Health Organisation (WHO) has updated the International Classification of Diseases to version 11 (ICD-11) which was recently adopted for use by countries in 2019. ICD-11 can be used in Electronic Medical Records (EMR) systems with support of extended technologies like Application Program Interface (API). Integration of ICD-11 in Rwandan EMR (OpenMRS) in two health facilities was conducted in July-October 2019. Findings indicated that adapting ICD11-API in EMR is feasible. More than 50% of diagnoses were recorded using ICD-11. Healthcare providers perceived ICD-11 API as easy to learn and useful for harmonization of diagnosis, data reporting and insurance reimbursement. Integration of ICD-11 API in EMR can be scaled up to all hospitals for use in Rwanda and other countries using similar system.